Preface - O’Meara Ryk-Lakhman (UCL Journal of Law and Jurisprudence, 2016)
This issue champions the continued development of the UCLJLJ. 2015 was the first year to witness the publication of two issues of the Journal and we are proud to continue this tradition in 2016. Moreover, we pride ourselves on being at the forefront of the shift towards open access in academia. The UCLJLJ is one of the first law journals in the UK to offer equitable access to cutting-edge scholarship for any reader, anywhere. At the same time, the UCLJLJ remains true to its core values by offering a generalist publication on a variety of topics of law and jurisprudence that is open to practitioners and academics alike. Each of the seven papers assembled here offers an original contribution to a particular area of law or covers a subject that we hope is both topical and interesting to our readers. Please read the full Preface here: http://discovery.ucl.ac.uk/1493247/